Efektivitas Penggunaan Strategi Teams Games Tournament (TGT) Dalam Pembelajaran IPS Materi Keragaman Flora Dan Fauna Di Indonesia Kelas VII SMP N 2 Colomadu - Ni'am, Irjob Sholikun; , Drs. Dahroni, M.Si (2016)
SMP Negeri 2 Colomadu located at Pulosari stret, Village Malangjiwan Colomadu subdistrict, Karanganyar. Methods and strategies in learning is very diverse, for the teacher to be able to master a variety of methods and learning strategies. The method applied in teaching must involve the students to be more active in the learning process. The purpose of this study was to determine the effectiveness of the strategy Teams Games Tournament (TGT) on the material diversity of flora and fauna in Indonesia class VII SMP Negeri 2 Colomadu. The method in this research is experimental design with pretest posttest control design. The population of this study were 267 students of class VII SMP Negeri 2 Colomadu. The experimental group was the group receiving the learning process with a strategy Teams Games Tournament (TGT), while the control group is the group receiving the learning process using a strategy of lectures. The study concluded that (1) Use of strategies Teams Games Tournament (TGT) on the material diversity of flora and fauna in Indonesian students of class VII SMP N 2 Colomadu showed an increase in the average value of student learning outcomes at 47.38 which is the results of average value Pretest average rose 25.60 to 72.98 on the outcome of the average value of its posttest. (2) Judging from the Mann Whitney test showed a difference between the experimental class with a grade control, it is shown by the value Asymp. Sig. (2-tailed) was 0.000 <0.05, then from the experimental class and control class there are differences in learning outcomes of these two classes. Keywords: Effectiveness, Teams Games Tournament (TGT), learning outcomes.